Sex differences in hip osteoarthritis: results of a longitudinal study in 508 patients. Issue 10 (12th September 2003) - Maillefert, J F; Gueguen, A; Monreal, M; Nguyen, M; Berdah, L; Lequesne, M; Mazieres, B; Vignon, E; Dougados, M
Abstract : Objective: To evaluate sex differences in the clinical and structural presentation, and natural history of hip OA. Methods: A multicentre, prospective, longitudinal, five year follow up study of 508 patients (302 women, 206 men, mean age 63 (7) years) with painful hip OA. Data collected were baseline demographics, symptomatic, therapeutic, and structural variables; symptomatic variables and changes in joint space width (JSW) during the first year's follow up; requirement for total hip arthroplasty (THA) between the end of the first and fifth years. Statistical analysis: evaluation of sex differences ( a ) at baseline, in the main characteristics of hip OA using multivariate logistic regression; ( b ) during the first year of follow up, in the radiological progression of the disease; ( c ) during the five years of follow up, in the requirement for THA using Kaplan-Meier curves and the log rank test, and of the parameters related to THA, using a multivariate Cox analysis. Results: At entry, women presented more frequently than men with polyarticular OA (mean (SD) articular score 306 (162) v 235 (127)), and superomedial migration of the femoral head (40% v 19%), and had more severe symptomatic disease (patient's overall assessment 46 (23) v 40 (26)). The change in JSW did not differ between women and men after one year, but a greater proportion of women had rapid structural progression (OR=2.34, 95% CI 1.1 to 5.2). THA was performed more often in women. Multivariate analysis suggested that the decision to perform surgery was related more closely to the symptomatic and structural severity of the disease than to the sex of the patient. Conclusion: Hip OA in women is more frequently part of a polyarticular OA, and displays greater symptomatic and structural severity.